Amorphous Red Phosphorus Embedded in Sandwiched Porous Carbon Enabling Superior Sodium Storage Performances. Issue 12 (5th February 2018) - Wu, Ying; Liu, Zheng; Zhong, Xiongwu; Cheng, Xiaolong; Fan, Zhuangjun; Yu, Yan
Abstract: The red P anode for sodium ion batteries has attracted great attention recently due to the high theoretical capacity, but the poor intrinsic electronic conductivity and large volume expansion restrain its widespread applications. Herein, the red P is successfully encapsulated into the cube shaped sandwich‐like interconnected porous carbon building (denoted as P@C‐GO/MOF‐5) via the vaporization–condensation method. Superior cycling stability (high capacity retention of about 93% at 2 A g −1 after 100 cycles) and excellent rate performance (502 mAh g −1 at 10 A g −1 ) can be obtained for the P@C‐GO/MOF‐5 electrode. The superior electrochemical performance can be ascribed to the successful incorporation of red P into the unique carbon matrix with large surface area and pore volume, interconnected porous structure, excellent electronic conductivity and superior structural stability. Abstract : The red P encapsulated into the cube shaped sandwich‐like interconnected porous carbon building (denoted as P@C‐GO/MOF‐5) is fabricated via the vaporization–condensation method. When used as anode material for sodium ion batteries, superior cycling stability (high capacity retention of about 93% at 2 A g −1 after 100 cycles) and excellent rate performance (502 mAh g −1 at 10 A g −1 ) are obtained.